Magnetic resonance imaging/transrectal ultrasonography fusion targeted prostate biopsy finds more significant prostate cancer in biopsy‐naïve Japanese men compared with the standard biopsy. (16th November 2019) - Fujii, Shinsuke; Hayashi, Tetsutaro; Honda, Yukiko; Terada, Hiroaki; Akita, Ryuji; Kitamura, Naoyuki; Ueda, Eikoh; Han, Xiangrui; Ueno, Takeshi; Miyamoto, Shunsuke; Kitano, Hiroyuki; Inoue, Shogo; et al.
Abstract : Objective: To assess the clinical benefits of magnetic resonance imaging/transrectal ultrasound fusion‐targeted biopsy for biopsy‐naïve Japanese men. Methods: Between February 2017 and August 2018, 131 biopsy‐naïve men who underwent targeted biopsy together with 10‐core systematic biopsy at Hiroshima University Hospital were retrospectively investigated. Multiparametric magnetic resonance imaging findings were reported based on Prostate Imaging Reporting and Data System version 2. Results: The overall cancer detection rates per patient were 69.5% in systematic biopsy + targeted biopsy cores, 61.1% in systematic biopsy cores and 61.1% in targeted biopsy cores. The detection rates for clinically significant prostate cancer were 43.5% in targeted biopsy cores and 35.9% in systematic biopsy cores ( P  = 0.04), whereas the detection rates for clinically insignificant prostate cancer were 17.6% and 25.2% respectively ( P  = 0.04). Lesions in the peripheral zone were diagnosed more with clinically significant prostate cancer (54.8% vs 20.7%, P  < 0.001) and International Society of Urological Pathology grade (3.2 vs 2.7, P  = 0.02) than that in the inner gland. Just 4.2% (3/71) of Prostate Imaging Reporting and Data System category 2 and 3 lesions in the middle or base of the inner gland were found to have clinically significant prostate cancer. The cancer detection rate per core was 42.3% in targeted biopsy cores, whereas it was 17.9% in systematic biopsy cores ( P  < 0.001). Conclusions: Targeted biopsy is able to improve the diagnostic accuracy of biopsy in detection of clinically significant prostate cancer by reducing the number of clinically insignificant prostate cancer detections compared with 10‐core systematic biopsy in biopsy‐naïve Japanese men. In addition, the present findings suggest that patients with Prostate Imaging Reporting and Data System category 2 or 3 lesions at the middle or base of the inner gland might avoid biopsies.